A growth strategy for “ITM Tor” LTD - Musayeva, Lala (ADA University, 2020)
The introduced paper is a consultancy work realized with a local for-profit company “ITM Tor”, which was established in 2015. The staff of the company mainly come from “Main Accounting Center” – The State Statistics Committee, which was abolished in accordance with the decision of the Cabinet of Ministers of the Republic of Azerbaijan. Although almost all the employees came from the government organization, currently the company has no government intervention, operates in the private sector and charge for its services. The scope of services the company provides are providing technical and software solutions by conducting research on the application of modern IT in enterprises and organizations, developing and putting into operation software tools and, if necessary, supporting those systems, conducting trainings for faster implementation of solutions in organizations, application of web solutions, implementation of works such as development and installation of data network topology, application of effective databases and server systems, application of cloud technology. The main competitive advantage of the company is that the products and services the company offers are based on an open system, with no necessity of investing in price-heavy hardware making “ITM Tor” the only IT company in Azerbaijan in this respect. Unfortunately, the company’s annual sales revenue has been decreasing, which is mainly due to decreasing clientele. Hence, the company has a strong desire to improve the performance and to grow its business. The objective of this paper is to answer the following question: ➢ “What is the most appropriate growth strategy for “ITM Tor” in Azerbaijan?” In order to answer this question, it is necessary to understand the current state of the company. Thus, a thorough analysis of the company was carried out. To start with, the diagnosis of the company is performed. The first step while diagnosing, is the assessment of the external environment, which is performed through strategic tools such as PESTEL, Porter’s Five Forces and two customer satisfaction surveys . Then primary data was collected for the internal analysis of “ITM Tor”, which then was combined with the results of SWOT analysis. Here the primary data included qualitative data, such as interviews with four employees of the company, and quantitative data- an employee satisfaction survey. Overall three surveys were created: one for current customers, the second one for future potential customers and the third for employees of “ITM -Tor”. The surveys helped to better analyze the customer satisfaction level and their requirements. The next step was to choose the best growth model and strategy according to the collected data. In the end, discussion part was developed and recommendations were discussed accordingly.
Keywords: Business; Information technology -- Azerbaijan.; Employee satisfaction -- Azerbaijan.; Customer satisfaction -- Azerbaijan.